Childhood intelligence and the emergence of self-control - Petkovsek, Melissa A. (Criminal justice and behavior, 2014)
Self-control represents, perhaps, one of the most robust predictors of antisocial behavior uncovered by behavioral scientists. What remains more unclear, however, are the exact sources of individual differences in levels of self-control. Emergent evidence along these lines is beginning to suggest that levels of intelligence?another robust correlate of antisocial behavior?may play an important role in predicting the development of self-control. Moreover, the influence of intelligence may begin to manifest very early in development. Building on prior work, the current study seeks to explore the role of intelligence in predicting levels of self-control in children. Our findings suggest that higher levels of intelligence predict higher levels of self-control beyond other traditional criminological and sociological variables including parenting practices and parental levels of self-control. These findings further underscore the relevance of intellectual functioning for a host of impactful traits in humans.